The species composition of herbivorous acarofauna in the south of Western Siberia - Ekaterina Ulyanova; Irina Andreeva; Elena Shatalova (Persian Journal of Acarology)
As the species composition and distribution of spider mites and eriophyid mites in the open ground of the Siberian region are not actually studied, this line of research was the purpose of our work.